Bacterial, but not fungal, communities show spatial heterogeneity in European beech (Fagus sylvatica L.) deadwood - Bosch, Jason; Némethová, Ema; Tláskal, Vojtěch; Brabcová, Vendula; Baldrian, Petr (FEMS microbiology ecology, 2023)
Deadwood decomposition and other environmental processes mediated by microbial communities are generally studied with composite sampling strategies, where deadwood is collected from multiple locations in a large volume, that produce an average microbial community. In this study, we used amplicon sequencing to compare fungal and bacterial communities sampled with either traditional, composite samples, or small, 1 cm3 cylinders from a discrete location within decomposing European beech (Fagus sylvatica L.) tree trunks. We found that bacterial richness and evenness is lower in small samples when compared to composite samples. There was no significant difference in fungal alpha diversity between different sampling scales, suggesting that visually defined fungal domains are not restricted to a single species. Additionally, we found that composite sampling may obscure variation in community composition and this affects the understanding of microbial associations that are detected. For future experiments in environmental microbiology, we recommend that scale is explicitly considered as a factor and properly selected to correspond with the questions asked. Studies of microbial functions or associations may require samples to be collected at a finer scale than is currently practised.
Keywords: mikrobiota; bacteria; stromy; Fagus; Mycobiome; Fungi; Trees; Bacteria; houby; fungi; microbial communities; mykobiom; buk (rod); temperate forest; wood decay; Microbiota; ecology; deadwood